Kesantunan Tindak Tutur Menyuruh oleh Orang Tua kepada Anak dalam Bahasa Jawa - Febuana Rosita; Ngusman Abdul Manaf (Jurnal Bahasa dan Sastra, 2023)
Javanese politeness theory and language learning lack comprehensive understanding of politeness principles in ordering speech acts outside Java island. This study aims to fill this gap by analyzing politeness strategies used by Javanese parents in Kenagarian Sungai Duo when giving orders to their children. Employing a mixed-methods approach with qualitative and descriptive statistics, the research uncovered six politeness principles employed in parents' speech: generosity, humility, sympathy, wisdom, praise, and agreement. Notably, parents prioritize generosity (16.66%) and other strategies to soften their commands, creating a highly polite communication environment (97% compliance). These findings suggest a nuanced understanding of parent-child dynamics and Javanese politeness beyond the island's borders, opening doors for further investigation into regional variations and their impact on family communication.